A simple environment-friendly process for preparing high-concentration alkali lignin nanospheres. (March 2019) - Liu, Chao; Li, Youming; Hou, Yi
Graphical abstract: Highlights: High-concentration alkali lignin nanospheres were synthesized. The lignin nanospheres with no chemical modification are very stable at pH 4–10. This green lignin nanosphere is an effective way to utilize high value lignin. Abstract: Biomass nanomaterials based on aromatic ring monomers have broad application prospects in the fields of drug delivery, catalysis and environment. In this paper, based on the effective dissolution of commercial alkali lignin in imidazole ionic liquids, lignin nanospheres were rapidly prepared by adding anti-solvent of water. In the three imidazole ionic liquids (1-amyl-3-methylimidazolium acetate (C5mim][Ac]), 1-butyl-3methylimidazolium acetate ([Bmim][Ac]) and 1-ethyl-3-methylimidazolium acetate ([Emim][Ac])), lignin can dissolve well, and the dissolution rates are all >25%, which is much higher than other organic solvents. And the longer the alkyl chain in imidazole ring is, the lower the solubility of lignin is. The paper also studied the effects of lignin concentration, the addition rate of anti-solvent, stirring rate and pH on the size of lignin nanospheres. It was found that the lignin nanospheres prepared under suitable conditions have particle size in the range of 52–210 nm and have good stability for over two months. And, compared to other studied, the particle size of the nanospheres is much smaller and easier to control. Moreover, the quality of lignin nanospheres was elucidated by Fourier transform infrared spectroscopy (FT-IR), Gel permeation chromatography (GPC) and UV–vis spectroscopy (UV–Vis) measurements which found the molecular weight of lignin nanospheres was slightly lower the raw alkali lignin, and the main structure of the aromatic ring of lignin is preserved in the process of preparation of the nanospheres by ILs. The method of preparing lignin nanosphere from lignin-ionic liquids solution with water as anti-solvent is simple, rapid and environmentally friendly, and provides an efficient and feasible path for the high value utilization of lignin.